Health and safety management of lead in soil in U.S. Air Force bases - De Jesus, Ricardo (Kansas State University, 2014)
Urban soils contaminated with lead can pose a health risk if vegetables and fruits from the garden are consumed. In general, we don’t think our gardens as dangerous or toxic, but unfortunately some garden soils do contain toxic levels of lead. Chipping paint around older structures will raise the lead level in the soils directly adjacent to the building. Restrictions to lead paint started in the 1950’s. Today lead paint content has been reduced; however paint companies are allowed to mix up to 0.05% lead in paints. Lead use has been reduced significantly, but not entirely eliminated. Soil can be contaminated with lead from other sources such as industrial sites, industrial sludge with heavy metals, auto emissions, old lead plumbing pipes or even old orchard sites in production when lead arsenate was in use. The main concern with lead in firing ranges is the fate and transport of heavy metals from bullets fragments accumulating in soil. Of these metals, lead is the predominant contaminant. Lead is considered the top environmental threat to children’s health. The U.S. military alone has cleaned up more than 700 firing ranges across the country over the past several years. The U.S. Air Force conducted a study at Shaw Air Force base to determine the lead concentrations in ground water and soil collected from the Small Arms Firing Range in 1992. The purpose of this study was to determine the levels of contamination in the soil in order to develop a restoration plan. The goal of the restoration plan was to clean up the land for future use. The Defense Environmental Restoration Program (DERP) conducted a project at Beale Air Force Base to clean up contaminated lead soil and to prevent any future fine and environmental expenses for the base. The main goal was to protect the base population from the lead and other contaminants hazards. In 1992 the Air Force conducted an investigation that included environmental sampling of soil and lead of the Tyndall Elementary School grounds. The Air Force collected lead samples in areas where children play on the school ground. Because lead concentrations results were below the toxic levels for lead, the Air Force concluded that no further action was needed. Further investigation for soil removal took part in 1992 and 2009. Under the Critical Removal Action field activities included site preparation, waste characterization, investigative sample chemical analysis, contaminated soil excavation, dust control, disposal, backfill and grading, and site restoration. Over the years the Air Force has been able to educate the military community on health hazards in the base facilities especially lead exposure and have been able to implement programs dedicated to prevent any lead overexposure.
Keywords: Health management of lead in soil; Soil Sciences (0481)